Assessment of geneXpert test for diagnosis of pediatric pulmonary tuberculosis - Roma, Km; Shrestha, Suvesh Kumar; Bhandari, Nirajan; Shah, Gaurav Jung; Khetan, Shivam (Birat Journal of Health Sciences, 2023)
Introduction: Pediatric tuberculosis is an infectious disease and is a leading cause of death in Nepal. The incidence of pediatric TB is a key tool of ongoing transmission of tuberculosis within the community and vital indicator of disease control. Its diagnosis is very much challenging and delay in diagnosis leads to mortality.Objectives: This study was conducted to assess the utility of the gene Xpert test for diagnosis of pediatric pulmonary tuberculosis.Methodology: A hospital based prospective study done at Pediatric department of a teaching hospital, Nepalgunj, Banke conducted over a period of 1 year from 1 January 2021 to 31 December 2021 with presumptive diagnosis of pediatric pulmonary tuberculosis. Chi-square test was used to determine the association between categorical variables and a receiver operating curve (ROC) analysis was performed to compare the performance of gene Xpert test with other lab parameters like sputum/gastric lavage sample microscopy for acid fast bacilli, erythrocytic sedimentation rate, Tuberculin test (TT) and chest X-ray. Results: We enrolled a total of 294 patients in our study. Out of 294 samples 5.1% samples came out to be positive for gene Xpert for MTB. The sputum/gastric lavage samples for AFB showed both sensitivity and specificity of 100%. The tuberculin test showed a sensitivity of 80% and specificity of 37.3%. Chest X-ray showed a sensitivity of 66.7% and specificity of 43.7%. The area under the curve for acid fast bacilli in microscopy, tuberculin test and ESR was found to be 100% (95% CI: 100%-100%), 58.6% (95% CI: 44.9%-72.4%), and 52.6% (95% CI: 37%-68.3%) respectively.  Conclusion: This study highlights the utility of gene Xpert as a good diagnostic tool for rapid diagnosis of pulmonary tuberculosis in pediatric population.